Quality Issues in the Management of Web Information - Pasi, Gabriella; Bordogna, Gloria; Jain, Lakhmi C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This research volume presents a sample of recent contributions related to the issue of quality-assessment for Web Based information in the context of information access, retrieval, and filtering systems. The advent of the Web and the uncontrolled process of documents' generation have raised the problem of declining quality assessment to information on the Web, by considering both the nature of documents (texts, images, video, sounds, and so on), the genre of documents ( news, geographic information, ontologies, medical records, products records, and so on), the reputation of information sources and sites, and, last but not least the actions performed on documents (content indexing, retrieval and ranking, collaborative filtering, and so on). The volume constitutes a compendium of both heterogeneous approaches and sample applications focusing specific aspects of the quality assessment for Web-based information for researchers, PhD students and practitioners carrying out their research activity in the field of Web information retrieval and filtering, Web information mining, information quality representation and management.
Automated Cleansing of POI databases -- A Survey of Volunteered Open Geo-Knowledge -- Bases in the Semantic Web -- Fact Based Search Engine -- Quality-based knowledge discovery from medical text on the Web -- Challenges for search engine retrieval effectiveness evaluations: Universal Search and user intents, and results presentation -- Challenges for search engine retrieval effectiveness evaluations: Universal Search and user intents, and results presentation -- Challenges for search engine retrieval effectiveness evaluations: Universal Search and user intents, and results presentation.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).